2019
DOI: 10.1097/ta.0000000000002381
|View full text |Cite
|
Sign up to set email alerts
|

Promotility agents for the treatment of ileus in adult surgical patients: A practice management guideline from the Eastern Association for the Surgery of Trauma

Abstract: BACKGROUND Ileus is a common challenge in adult surgical patients with estimated incidence to be 17% to 80%. The main mechanisms of the postoperative ileus pathophysiology are fluid overload, exogenous opioids, neurohormonal dysfunction, gastrointestinal stretch, and inflammation. Management includes addressing the underlying cause and supportive care. Multiple medical interventions have been proposed, but effectiveness is uncertain. A working group of the Eastern Association for the Surgery of Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Smooth tends to bend closer together. There are many methods for MRI image segmentations, including manual, semiautomatic, and fully automatic segmentation [ 19 , 20 ]. Among them, manual segmentation is to directly outline the boundary with a pen on the image, and the segmentation result is completely determined by the practical experience of the segmenter, so the reliability is low.…”
Section: Discussionmentioning
confidence: 99%
“…Smooth tends to bend closer together. There are many methods for MRI image segmentations, including manual, semiautomatic, and fully automatic segmentation [ 19 , 20 ]. Among them, manual segmentation is to directly outline the boundary with a pen on the image, and the segmentation result is completely determined by the practical experience of the segmenter, so the reliability is low.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published practical guidelines evaluated usefulness of pro-motility agents for treatment of ileus in adult surgical patients. 76 Regarding erythromycin, four RCTs and one prospective study were included, [77][78][79][80][81] for a total of 128 patients treated with erythromycin and 140 patients in the control groups. Erythromycin had no effect on the resolution of ileus.…”
Section: Postsurgical Ileusmentioning
confidence: 99%
“…Postoperative ileus (POI) is characterized by bowel dysmotility and patient distress following major gynecological oncology surgeries, affecting 10%-50% of patients. 1,2 It is associated with postoperative nausea, vomiting, abdominal pain, delayed discharge, long-term opioid use, increased readmission rate, and high inpatient economic burden. 3 A recent study found that POI increases hospital costs by an average of 71% per patient.…”
Section: Introductionmentioning
confidence: 99%